PERENCANAAN KOMUNIKASI MATAHARI KECIL SEBAGAI ORGANISASI NON-PROFIT DALAM MENDAPATKAN DONASI - Rizkia Dinanti; Rah Utami Nugrahani (Jurnal Komunikasi, 2019)
ABSTRACTCommunication planning is one of the most important aspects of achieving goalswithin acompany. In a non-profit organization,donationsare urgently needed for the organization’s sustenance. Mataharikecil, with a “Spreading goodness” tagline is a non-profit organization meant to spread good to street children with a social background of preaffluent families in order to further education. This research title’s is Marketing Communication Strategy as a non-profit organization for donations. This research was find out how Mataharikecil plan can make a such donations that help children who can’t continue their schooling further. It used a qualitative method with a descriptive approach and used a constructive paradigm. Data collecting techniques used under observation, interviews, and documentation. This interview is conducted with three internal individuals focused in the small solar donation to explain the communication planning. The result of this research is what kindofstrategyMataharikecilusestogetdonations